Pemberdayaan lansia melalui program deteksi dini gangguan fungsi kognitif - Widyaningsih, Heriyanti; Lestyari, Sri Indah; Yuliana, Alvi Ratna; Wanarsih, Biyanti Dwi; Hartini, Sri; Faridah, Noor (Jurnal PADE: Pengabdian & Edukasi, 2024)
Cognitive function is one of the problems that occurs in the elderly because physiologically as a person ages they will experience a decrease or disturbance in their nervous system due to disrupted oxygen supply to the brain, degenerative disease, Alzheimer's disease, malnutrition and impaired cognitive function including orientation to time, space, place and things. something new that is difficult to accept. Risk factors that can influence the decline in cognitive function are family heredity, level of education, brain injury, toxins, not doing physical activity, and chronic diseases such as Parkinson's, heart disease and stroke. This activity involves the elderly with the aim of early detection of cognitive dysfunction in Dukuh Kadilangon, Gondangmanis Village, Bae District, Kudus Regency. The results of the Screening in Dukuh Kadilangon, Gondangmanis Village, showed normal cognitive function in the elderly as many as 10 people (24.4%), mild cognitive impairment as many as 11 people (26.8%), moderate cognitive impairment in 17 people (41.5%), and 3 people (7.3%) had severe cognitive impairment. Conclusion: The cognitive function of the elderly in Dukuh Kadilangon, Gondangmanis Village, Bae District, Kudus Regency, results show that the majority of elderly people have moderate cognitive dysfunction, 17 people (41.5%).